2011
DOI: 10.1103/physrevb.83.155102
|View full text |Cite
|
Sign up to set email alerts
|

Doping properties of monoclinic BiVO4studied by first-principles density-functional theory

Abstract: The intrinsic and extrinsic doping properties of BiVO 4 , i.e., the formation energies and transition energy levels of defects and impurities, have been studied systematically by first-principles density-functional theory. We find that for doping caused by intrinsic defects, O vacancies are shallow donors and Bi vacancies are shallow acceptors.However, these defects compensate each other and can only lead to moderate n-type and p-type conductivities at Bi-rich and O-rich growth conditions, respectively. To obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
134
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(144 citation statements)
references
References 44 publications
10
134
0
Order By: Relevance
“…As described above, native defect theory would predict that material synthesized under Orich conditions, which is the typical environment used for formation of BiVO 4 , should exhibit p-type character. 18 Our finding that hydrogen defects are present in as-synthesized BiVO 4 can explain the experimental observation that as-grown BiVO 4 is nearly always n-type. 8 The source of this hydrogen could be from decomposition of metal-organic precursors during formation and/or from water in the annealing environment, which is often laboratory air.…”
Section: Hydrogen Incorporation In Bivosupporting
confidence: 70%
See 1 more Smart Citation
“…As described above, native defect theory would predict that material synthesized under Orich conditions, which is the typical environment used for formation of BiVO 4 , should exhibit p-type character. 18 Our finding that hydrogen defects are present in as-synthesized BiVO 4 can explain the experimental observation that as-grown BiVO 4 is nearly always n-type. 8 The source of this hydrogen could be from decomposition of metal-organic precursors during formation and/or from water in the annealing environment, which is often laboratory air.…”
Section: Hydrogen Incorporation In Bivosupporting
confidence: 70%
“…In particular, density functional theory (DFT) calculations by Yin et al predict that BiVO 4 should have p-type character when synthesized under O-rich conditions and n-type character when synthesized under O-poor/Bi-rich conditions. 18 In contrast, experimentally synthesized films, which are typically annealed at high temperature for long times in oxygen or air (i.e. under O-rich conditions), consistently exhibit n-type conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 Previous experimental works have reported band gaps in the 2.4-2.6 eV range of monoclinic BiVO 4 and theoretical calculations based on density functional theory (DFT) using standard GGA exchange-correlation functional like Perdew-Burke-Emzerhof (PBE) were performed for validation attempts. 15,22 However, more accurate calculations using hybrid functionals like HeydScuseria-Ernzerhof (HSE06) predicted a band gap energy around 3.0 eV. 23 This observation was surprising because semi-local GGA functionals generally strongly underestimate the band gap of semiconductors, while hybrid functionals like HSE06 are well known to give better agreement with experiment.…”
Section: Introductionmentioning
confidence: 94%
“…13 Doping by introducing an extrinsic defect through the addition of a transition-metal cation or an anion can increase the carrier density and thus improve the conductivity for optimum photocatalytic performance. Following 4 this strategy, numerous studies and research efforts have been focused on doping BiVO 4 with Mo and W. [14][15][16][17] This effect has been extended as well to intrinsic doping defined as native defects. Some studies suggested that this oxide can be stoichiometric at 1 atmospheric oxygen pressure, while oxygen vacancies might be created in reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…18 Incorporation of Mo into BiVO 4 increases the carrier density and distorts the VO 4 tetrahedron, resulting in a local internal electric field. 19 It has also been observed that Mo is better suited than the commonly used W for the n-type doping of BiVO 4 . 20 In this work, we systematically investigated the deposition of BiVO 4 films by a reactive magnetron sputtering process.…”
Section: Introductionmentioning
confidence: 99%